Using limiting similarity to enhance invasion resistance: Theoretical and practical concerns. Issue 3 (20th December 2019) - Hess, Manon C. M.; Buisson, Elise; Jaunatre, Renaud; Mesléard, François
Abstract: The control of invasive species is a central topic of both applied and theoretical research. Understanding how and which ecological theories can be used to improve invasion resistance of plant communities is essential, to design effective control strategies. The theory of limiting similarity, stating that coexistence between species is more limited by competitive exclusion when species share niche properties, is often considered by applied ecologists as a possible approach to limiting plant invasions at the local scale. The complexity of measuring ecological niche overlap between species as well as the difficulty of disentangling niche from fitness processes currently limit the demonstration and application of this theory. Limiting similarity appears to operate at a time‐scale that is too long for efficient impact on invasive species' early establishment. It may also be ineffective against invasions in the long term, due to environmental changes and community instability. Finally, limiting similarity is not applicable to the most common situations, where there are multiple co‐occurring invasive species or no prior identification of potential invasives. Synthesis and applications . Whether the theory of limiting similarity, predicting competitive exclusion when species display niche similarities, can be successfully applied to limit plant invasions—or not—is an important issue for practitioners facing invasive species. In practice, using limiting similarity to design invasion‐resistant plant communities appears to be complex, ineffective and unsuitable for most common situations. Abstract : Whether the theory of limiting similarity, predicting competitive exclusion when species display niche similarities, can be successfully applied to limit plant invasions—or not—is an important issue for practitioners facing invasive species. In practice, using limiting similarity to design invasion‐resistant plant communities appears to be complex, ineffective and unsuitable for most common situations.